The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1034/j.1399-3038.2002.02081.x
|View full text |Cite
|
Sign up to set email alerts
|

Domestic aeroallergen levels in Barcelona and Menorca (Spain)

Abstract: Exposure to common indoor allergens is known to be associated with sensitization and triggers of asthma. Levels of allergens have been barely described in Mediterranean countries. This study reports domestic allergen levels among the general population of two regions of Spain. Dust samples were collected from living rooms and mattresses in homes of infants in Barcelona (n = 366) and Menorca (n = 475) and assayed for house dust mite (Der p 1) and cat allergen (Fel d 1) concentrations by enzyme-linked immunoabso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
12
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 17 publications
4
12
1
Order By: Relevance
“…While analyzing the concentrations of allergens obtained by other researchers in similar studies it must be noted that the results vary depending on the country and the test sample. Comparing them to the allergen concentrations reported in our study, it should be noted that the average values donot correspond well with the results of similar works by other authors [19,43]. Topp et al, in the research conducted over a few years in Germany, indicated in the dust both from the floor and the bed lower concentration values, compared to ours, for Der p1, but higher for Fel d1 [31].…”
Section: Ijomeh 2013;26(6) 883contrasting
confidence: 33%
“…While analyzing the concentrations of allergens obtained by other researchers in similar studies it must be noted that the results vary depending on the country and the test sample. Comparing them to the allergen concentrations reported in our study, it should be noted that the average values donot correspond well with the results of similar works by other authors [19,43]. Topp et al, in the research conducted over a few years in Germany, indicated in the dust both from the floor and the bed lower concentration values, compared to ours, for Der p1, but higher for Fel d1 [31].…”
Section: Ijomeh 2013;26(6) 883contrasting
confidence: 33%
“…The gold standard method to measure mite allergens content is the enzymatic immunoassay (1, 8, 9). However, only few mite allergen extracts are currently available for immunoassays, mainly D. pteronyssinus , Dermatophagoides farinae , and Blomia tropicalis .…”
Section: Discussionmentioning
confidence: 99%
“…27 In what follows living room levels were used for the main analysis, although this was repeated with mattress samples, and a multivariate model including both was constructed. House dust mite allergen (Der p 1) and cat allergen (Fel d 1) concentrations were estimated from dust samples collected by the study team with the same vacuum cleaner equipped with an ALK filter (ALK, Maidstone, United Kingdom) and analyzed in a single laboratory by means of ELISA according to a standard protocol.…”
Section: Abbreviations Used Amics: Asthma Multicenter Infant Cohort Smentioning
confidence: 99%
“…House dust mite allergen (Der p 1) and cat allergen (Fel d 1) concentrations were estimated from dust samples collected by the study team with the same vacuum cleaner equipped with an ALK filter (ALK, Maidstone, United Kingdom) and analyzed in a single laboratory by means of ELISA according to a standard protocol. 27,28 In the 4-year blood sample specific IgE levels against Der p 1, Fel d 1, and mixed grass pollens were determined in the same laboratory by using UniCap (Pharmacia, Morris Plains, NJ).…”
Section: Abbreviations Used Amics: Asthma Multicenter Infant Cohort Smentioning
confidence: 99%
See 1 more Smart Citation